Pengaruh Menu Knowledge Pramusaji Terhadap Keterampilan Personal Selling Di Restoran Cinnamon, Hotel Mandarin Oriental Jakarta - Agung Gita Subakti (Journal of Indonesian Tourism, Hospitality and Recreation, 2022)
ABSTRACTThe objective of this research is to determine the influence of waiter’s/waitress’ menu knowledge on his/her personal selling skill at Cinnamon Restaurant, Mandarin Oriental Hotel Jakarta. The quantitative method was used by collecting data from sample of 14 respondents who were the waiter/waitress of Cinnamon Restaurant, Mandarin Oriental Hotel Jakarta, and also using interviews and literature study. Analysis used in this research is descriptive analysis and simple linear regression analysis. The results of this research show that waiter’s/waitress’ menu knowledge has a positive influence on his/her personal selling skill. Conclusions of this research, there was a significant influence between waiter’s/waitress’ menu knowledge on his/her personal selling skill at Cinnamon Restaurant, Mandarin Oriental Hotel Jakarta of 87,5% with correlations coefficient of 0.936.   ABSTRACTTujuan dari penelitian ini adalah untuk menganalisa pengetahuan menu pramusaji pada keterampilan penjualan di Restoran Cinnamon, Hotel Mandarin Oriental, Jakarta. Metode kuantitatif digunakan dengan mengumpulkan data dari sampel 14 responden yang merupakan pramusaji Cinnamon Restaurant, Jakarta, dan juga menggunakan wawancara dan studi literatur. Analisis yang digunakan dalam penelitian ini adalah analisis deskriptif dan analisis regresi linier sederhana. Hasil penelitian ini menunjukkan bahwa pengetahuan menu pramusaji memiliki pengaruh positif pada keterampilan penjualan pribadinya. Kesimpulan dari penelitian ini, ada pengaruh signifikan antara pengetahuan menu pelayan / pelayan tentang keterampilan penjualan di Cinnamon Restaurant, Jakarta sebesar 87,5% dengan koefisien korelasi 0. 936.